What are the main drivers of SMEs’ production of sustainability reports? - M. Dolores Guerrero-Baena; Francisca Castilla-Polo; Pablo Rodríguez-Gutiérrez (Small Business International Review)
This study aims to deepen our understanding of the theoretical frameworks that underlie SMEs' disclosure of sustainability information. Qualitative empirical research was conducted on SMEs that proactively engage in sustainability reporting. To identify the key drivers, interviews were conducted with a sample of Spanish SMEs, and the reasons for sustainability reporting provided by informants were ranked by frequency. Our findings indicate that stakeholder theory holds a prominent position, closely followed by legitimacy theory and the resource-based view. This ranking reveals a mixture of external and internal drivers, contributing to the existing literature by emphasizing the predominance of management factors over sociological arguments in favor of sustainability reporting in SMEs. Regulators, practitioners, and academics can benefit from these findings to better understand the decision-making processes of SMEs regarding sustainability reporting practices, while accounting for their relationships in the contexts in which they operate.